Evaluation of photovoltaic powered air conditioner system - Mohd Adzrie Bin Hj Radzali (School of Electrical System Engineering , University Malaysia Perlis, 2015)
In this research, evaluation on the performance of direct current air conditioning is carried out. Generation of solar energy systems have been studied and analyzed. Study and analysis done are on the production of electricity from photovoltaic modules as well performance and stability of the entire system through experimental setup. The objectives of this research is to obtain and assess solar radiation as potential electrical energy, design and optimize the air conditioner system to be operated using direct current from the energy generated by photovoltaic system. The air conditioner system used a compressor of 500 W which required 24 V DC to operate where the system could be running on a small supply voltage. This will reduce the electricity usage since it can operate within a stable and long-term period using free electricity generated by photovoltaic system. 16 units of 21 V 62 W photovoltaic modules act as the main source for supplying electricity to the air conditioning system by charging six units of 12 V 100 Ah batteries and to stabilize the system. The parameters tested and analyzed are voltage, current and power generated from photovoltaic modules and air conditioner system. The study covers theoretical analysis from designing to full installation of air conditioning systems complete with photovoltaic modules. With average annual solar radiation of 4.65 kWh/m2, it is possible to install the DC air conditioner system as the value shows that Perlis has the potential in generating enough electricity for small energy requirement. In addition, the photovoltaic system is one of the best methods in generating electricity for remote areas.